A pilot cohort study of deprescribing for nursing home patients acutely admitted to hospital. (June 2019) - Russell, Patrick; Laubscher, Sara; Roberts, Gregory W.; Mangoni, Arduino A.; McDonald, Cameron; Hendrix, Ivanka; Hewage, Udul; Hofmann, Dirk; Michell, Sophie; Taeuber, Lauren; Woodman, Richard J.; Shakib, Sepehr; et al.
Background: Patients from residential aged care facilities are commonly exposed to inappropriate polypharmacy. Unplanned inpatient admissions can provide an opportunity for review of complex medical regimens and deprescribing of inappropriate or nonbeneficial medications. The aim of this study was to assess the efficacy, safety and sustainability of in-hospital deprescribing. Methods: We followed a prospective, multi-centre, cohort study design, with enrolment of 106 medical inpatients age 75 years and older (mean age was 88.8 years) who were exposed to polypharmacy prior to admission and with a planned discharge to a nursing home for permanent placement. Descriptive statistics were calculated for relevant variables. The Short Form-8 (SF-8) health survey was used to assess changes in health-related quality of life (HRQOL) at 90-day follow up, in comparison with SF-8 results at day 30. Results: Deprescribing occurred in most, but not all patients. There were no differences between the groups in principal diagnosis, Charlson index, number of medications on admission or number of Beers list medications on admission. At 90 days, mortality and readmissions were similar, though the deprescribed group had significantly higher odds of better emotional wellbeing than the nondeprescribed group [odds ratio (OR) = 5.08, 95% confidence interval (CI): 1.93, 13.39; p  = 0.001]. In the deprescribing group, 31% of the patients still alive at 90 days had medications restarted in primary care. One-year mortality rates were similar. Conclusions: Deprescribing medications during an unplanned hospital admission was not associated with mortality, readmissions, or overall HRQOL.